AKRAB Analisis Semiotika Kritik Ideologi Dalam Film “Istirahatlah Kata-Kata” - Oktafiani Herlina (Jurnal Ilmu Komunikasi AKRAB, 2017)
Abstract"Istirahatlah Kata-Kata" tells the story of Wiji Thukul in his fugitive time in Pontianak. During his escape in Pontianak, Wiji felt anxious, scared and worried by his status. Initially, he isolates himself from the outside. Meanwhile, his wife and children had to face intimidation from agency to find out his whereabouts. This film criticize the ideology show in some dialogues and visual displays. This research analyse some scenes in the movie using semiotic approach to search the critique of ideology signified and the series of signs that construct the film, like the iconic signs, linguistic signs and musical signs. The result showed that this film uses iconic signs such as images, original sound like animal sounds at night, the sound of children crying, the sound of boots, and musical illustrations to reinforce the narrative story. This film also uses a linguistic signs as a symbolic dialogue, monologue, subtitle, and narration. Musical signs obtained from the poetry musical, verbal signs, and narrative story to give the historical background. Cinematic coded obtained by the use of voice over, motion pictures, and montage. This cinematic code consists of cinematographic plan code that is obtained through the structure of image, like image captures, angle shots, and long shots. The time code obtained from narrative films, the order time, and duration. Montage code obtained from editing and transitions. Shooting angle Code obtained through shooting distance and shooting angle. Space codes tells where this moment happened like Pontianak, Solo, Kapuas river, motels, wine shop, a darkroom, and optical effects code obtained through the lens focus.Keywords: Wiji Thukul, Istirahatlah Kata-Kata, biographical motion film, semiotic